Hepato-pancreatic fat-fetuin A based axis in context of diabetes and its reversal - B., Jayakrishnan (International Journal of Advances in Medicine, 2022)
Recent research has focused on reversing type 2 diabetes mellitus (T2DM) via lifestyle-related approaches, including low-calorie diets. Metabolic parameters such as fat accumulation in the liver and pancreas have garnered much attention in this context. Pancreatic fat has been linked with adverse metabolic consequences including T2DM and metabolic syndrome. Obesity is the primary factor leading to ectopic fat in organs such as the liver and pancreas. This review examines the potential role of pancreatic fat in the pathogenesis of T2DM and whether it can be a potential target in reversing this chronic condition.